Relationships among output, wages, productivity and employment in the Malaysian electronic and electrical sub-sector - Yusop, Zulkornain; Law, Siong Hook; Mohd Nor, Norashidah (Universiti Putra Malaysia Press, 2005)
The Malaysian electronic and electrical sub-sector has been the most important component of the nation's manufacturing sector. As is widely known, the sector has played a vital role in the nation's export, employment as well as overall economic growth. Considering the importance of the sub-sector, it is imperative that we ensure sustainable growth of the sub-sector and that competitiveness is maintained or even improved. This study is particularly aimed at investigating the linkages between output, productivity, wage and labour. As is widely acknowledged, wages may increase as long as it is commensurate with a higher increase in productivity. However, changes in wages can actually affect employment. Unit root tests indicate that all of the above variables are 1(1). Johansen's procedure was conducted to see the long run and short run relationships between the variables. The Johansen cointegration test results revealed that a long-run equilibrium relationship exists among the variables. From the short run dynamic analysis, we found that except for real wages, labour productivity and employment are statistically significant in influencing output.